Role of stress and ameliorative effects of resveratrol on pathophysiological changes associated with experimental Brucella melitensis infection in non-pregnant boer does - Polycarp, Tanko (2016)
Brucellosis is one of the most common zoonosis in the world. Information on the role of stress on the pathogenesis and/or immuno-pathology of this zoonotic disease is limited. This study investigated the shedding routes and pattern, serological responses, oxidative status and immuno-pathological derangements associated with Brucella melitensis infection in non-pregnant does subjected to road transportation-induced stress and dexamethasone-induced stress. The study involved four phases of experiments, which included road transportation (phase 1), road transportation with B. melitens is inoculation (phase 2), dexamethasone treatment withB. melitensis inoculation (phase 3) and B. melitensis inoculation with dexamethasone administrationand resveratrol treatment (phase 4). In phase 1, 35apparently healthy Boer does, aged 2 - 3, weighing 20 - 25 kg were randomly divided into two groups designated A and B of 30 and 5 animals respectively. Group A was transported for 7 h at 50 km/h, while group B was not subjected to transportation stress and served as control. Blood samples were collected at regular intervals (before transportation, 3.5 h on transit, immediately after transportation, days 3, 7, 16 and day 26) for assaying oxidative stress alongside haematological parameters. In phase 2, two set of experiments were conducted with 18 non-pregnant does each. In both 1st and the 2ndexperiments of phase 2, the goats were randomly divided into groups A, B and C of 6 goats each. In the 1st experiment, group A was transported on a road for about 3 h at 70 km/h prior to being inoculated with 107 CFU of B. melitensisocularly while group B was not transported but inoculated with similar dose of B. melitensis as in A above as positive control and group C was negative control. However, in the 2nd experiment, similar dose of B. melitensis was ocularly inoculated 30 minutes prior to road transportation while groups B and C wereused as positive and negative controls as in the 1st experiment. In phase 3, two sets of experiments were also conducted with 18 non-pregnant does in each of the experiment.The goats were similarly divided into 3 groups, A, B and Cin each of the experiment.In the 1st experiment, group A wasadminstered dexamethasone at 2 mg/kg for 7 days prior tobeing inoculated with 107 CFU of B. melitensis ocularly while group B was not administered with dexamethasone but inoculated ocularly with similar dose of B. melitensis as in A above and group C was inoculated with normal saline as negative control. In the 2nd experiment, the group A was inoculated ocularly with similar doses of B. melitensisas in 1st experiment above 30 minutes prior to dexamethasone adminstration. Group B was not adminstered dexamethasone but inoculated ocularly with similar dose of B. melitensis as in A above while group C was inoculated normal saline as negative control. In phase 4, 12 non-pregnant goats were randomly divided into 4 groups A, B, C and D of 3 animals each. Groups A and B were inoculated ocularly with 107 CFU of B. melitensis 3 weeks prior to 7 days administration of dexamethasone (2 mg/kg). Groups A wasn furthertreated with resveratrol for 5 days from week 4 post B. melitensis inoculation. Group C was not treated but inoculated with similar dose of B. melitensis ocularly as positive controlwhile group D was inoculated normal saline as negative control. In phases 2, 3 and 4, blood, nasal, ocular and vaginal swabs were collected at regular intervals for PCR, serological (RBPT and iELISA) and oxidative stress analysis. Three animals from each group were sacrificed at days 21 and 42 post inoculation (pi) in phases 2 and 3. However, the does in phase 4 were only sacrificed at day 42 pi. Selected tissues were collected for bacterial detection, immunohistochemistry and histopathological examination and cellular changes were scored and analysed. In this study, 7 hours of road transportation induced significant haematological derangement and oxidative stress. The significant haematological derrangements included neutrophilia and increase in neutrophil/lymphocyte ratio. Stress biomarkers such as MDA were found to be elevated while SOD and GSH were found to decrease consequential to 7 hour road transportation. In both phases 2 and 3, groups A shed the bacterium significantly (P< 0.05) higher compared togroup B. However, the shedding was highest in the 1stexperiment of phase 3. Both transportinduced (phase 2) and dexamethasone-induced stress (phase 3) were observed to significantly prolong the period and rate of shedding. While dexamethasone administration from day 21 post inoculation was noted to stimulate increase in the duration and rate of shedding, treatment with resveratrol significantly reduced shedding duration and rate. Dexamethasone administration was observed to induce oxidative stress which correlated with the intensified pathologies. The uterus and vagina of both groups A and B in phase 2 and 3 revealed mild infiltration of inflammatory cells and microgranuloma while extensive necrosis were observed in the lymph nodes, predominantly the mandibular and pre-scapular lymph nodes. In both phases 2 and 3, necrosis, periportal lymphocytic infiltration, microgranuloma and congestion were observed predominantly in group A at day 21 pi. Lesion score showed group A was significantly different (P< 0.05) compared to groups B and C in both phases 2 and 3. Mild to moderate immunostaining in the liver, kidneys and lungs and in red and white splenic pulps predominantly at day 21 pi in phase 2,while moderate to strong immunostaining was observed in group A in phase 3. Scoring of the immunostaining revealed significant difference between the groups in phases 2 and 3 experiments, with the highest significance observed phase 3. While dexamethasone administration from day 21 pi was also shown to increase the rate of immunoreactivity, treatment with resveratrol from day 28 pi was observed to induce a decline in immunostaining intensity and histopathological changes. This study demonstrated that road transportation stress and dexamethasone-induced stress, prolonged bacterial shedding, with the peak period of shedding between day 10 and day 14 pi. While B. melitensis infection produced no significant pathological alterations in the reproductive organs, significant pathological alterations were observed in liver, lungs and the kidneys. Although pathological lesions such as microgranuloma, periportal lymphocytic infiltration and necrosis in the liver and lungs are not pathognomonic to Brucella infection, these lesions were consistently observed in this study and it was therefore proposed that they should not be excluded in the differential diagnosis, should these lesions be observed.Treatment with resveratrol following dexamethasone administration was seen to significantly ameliorate damage induced by dexamethasone administration. This perhaps shows the usefulness of antioxidants in mitigating the effects of stress as well as improving the health of farm animals.